2017
DOI: 10.1017/s0007114517002446
|View full text |Cite
|
Sign up to set email alerts
|

Dietary zinc addition influenced zinc and lipid deposition in the fore- and mid-intestine of juvenile yellow catfishPelteobagrus fulvidraco

Abstract: The present study explored the mechanisms of dietary Zn influencing Zn and lipid deposition in the fore- and mid- intestine in yellow catfish Pelteobagrus fulvidraco, and investigated whether the mechanism was intestinal-region dependent. For this purpose, yellow catfish were fed three diets containing Zn levels of 8·83, 19·20 and 146·65 mg Zn/kg, respectively. Growth performance, intestinal TAG and Zn contents as well as activities and mRNA expression of enzymes and genes involved in Zn transport and lipid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
3
17
0
Order By: Relevance
“…The in vitro study found that the protein level of MTF1 and the mRNA levels of Zn transport genes (znt5, znt7, mt, and mtf1) were higher in the nano-Zn group than in the ZnSO 4 group. These data indicated that these key genes and proteins mediated the Zn uptake, transport, and metabolism, in agreement with other studies [6,19]. Studies suggested that nano-Zn can be dissolved in the digestive tract and accordingly release Zn 2+ [20].…”
Section: Discussionsupporting
confidence: 90%
“…The in vitro study found that the protein level of MTF1 and the mRNA levels of Zn transport genes (znt5, znt7, mt, and mtf1) were higher in the nano-Zn group than in the ZnSO 4 group. These data indicated that these key genes and proteins mediated the Zn uptake, transport, and metabolism, in agreement with other studies [6,19]. Studies suggested that nano-Zn can be dissolved in the digestive tract and accordingly release Zn 2+ [20].…”
Section: Discussionsupporting
confidence: 90%
“…After filtration (Whatman filter), the volume was increased to 50 ml with demineralised water prior to analysis, according to the method of Gheisari et al (27) ; egg white or yolk was defrosted, mixed and 0•5 g was placed in a plastic high-pressure tube for digestion (7 ml of nitric acid and 2 ml of hydrochloric acid) using an organic program. After cooling, the samples were transferred to 100 ml flasks and brought to 100 ml volume with deionised water for the homogenisation (28) ; Zn contents in serum, ovary, magnum and ESG were measured according to the method of Chen et al (29) . Flame atomic absorption spectrophotometry was used in the determination.…”
Section: Eggshell Ultrastructure and Energy-dispersive X-ray Spectrosmentioning
confidence: 99%
“…Overestimates of bioavailability (100%) and the poor growth performance of fish fed semi‐purified diets might have underestimated micronutrient requirements of fish (Paripatananont & Lovell, ; Wang et al, ). Inhibited feed intake and growth seems to be more apparent for carnivorous fish species than omnivorous or herbivorous fish (Chen et al, ; Wang et al, ). Juvenile yellow catfish exhibited poor growth performance (only 1.11–1.25 g weight gain) when fed a casein‐based basal diet even when formulated with adequate (19.2 mg/kg) to excess levels (146.65 mg/kg) of Zn for 8 weeks (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibited feed intake and growth seems to be more apparent for carnivorous fish species than omnivorous or herbivorous fish (Chen et al, ; Wang et al, ). Juvenile yellow catfish exhibited poor growth performance (only 1.11–1.25 g weight gain) when fed a casein‐based basal diet even when formulated with adequate (19.2 mg/kg) to excess levels (146.65 mg/kg) of Zn for 8 weeks (Chen et al, ). In the present study, a semi‐purified basal diet with 130 g/kg krill meal as palatability enhancer and 7 g/kg sodium phytate as an original antinutritional factor, which usually chelates with and decreases the digestibility of minerals in feedstuff mixtures, was used (Konietzny & Greiner, ).…”
Section: Discussionmentioning
confidence: 99%